(untitled) (International Journal of Economics Management and Social Science, 2026)
A well-........... Maritime deck officer and port operations roles remain male-dominated professions with persistent underrepresentation of women and other marginalized groups, despite global human capital shortages and evidence that diversity enhances organizational performance. This mixed-methods study examined barriers to recruitment and retention of women and underrepresented groups in maritime technical roles through interviews with 86 participants (women in maritime roles, male colleagues, employers, educators, industry recruiters) and surveys with 523 maritime employees across deck operations, port management, and maritime education contexts. Qualitative findings identified multi-level barriers: institutional (limited dedicated recruitment targeting women, insufficient awareness of maritime career opportunities among female secondary students), workplace culture (masculinized language and norms, sexual harassment incidents, limited mentorship), family structure (difficulty combining maritime careers with family responsibilities), and career progression (glass ceiling effects limiting advancement, gender-based pay inequities). Quantitative analysis (Cronbach’s α=0.81 for workplace culture scale) revealed that women reported significantly lower workplace climate perceptions (mean 2.8/5.0 versus male mean 4.1/5.0, t(521)=-12.3, p<0.001), lower career satisfaction (3.2/5.0 versus 4.3/5.0, p<0.001), and higher career attrition intentions (48% of women versus 12% of men planning to leave profession within five years, χ²=64.2, p<0.001). An intervention pilot combining targeted recruitment of female cadets, workplace cultural change initiatives, mentorship programs for women, and family-supportive policies (flexible scheduling for family responsibilities, childcare support) showed measurable impact: 23% increase in female cadet recruitment, 34% improvement in women’s workplace climate perceptions post-intervention, and 31% reduction in women’s attrition intentions. Findings establish that maritime organizations can substantially improve diversity and inclusion through systematic attention to recruitment pathways, workplace culture, mentorship access, and family-supportive policies. Recommendations address maritime employers, maritime educators, industry associations, and government regulators regarding how to operationalize inclusive maritime workplaces that fully utilize available human talent. Keywords : Maritime diversity; Gender equity; Recruitment strategies; Workplace culture; Career retention; Inclusive organizations; Deck operations; Port management